2022
DOI: 10.1021/acs.est.1c05520
|View full text |Cite
|
Sign up to set email alerts
|

Residues of Cardiovascular and Lipid-Lowering Drugs Pose a Risk to the Aquatic Ecosystem despite a High Wastewater Treatment Ratio in the Megacity Shanghai, China

Abstract: The residues of pharmaceuticals in surface waters of megacities and ecotoxicological implications are of particular concern. In this study, we combined field investigations and model simulations to explore the contamination of cardiovascular and lipid-lowering drugs, one group of the most prescribed medications globally, in surface waters of a typical megacity, Shanghai, with a high wastewater treatment ratio (≈96%). Among 26 target substances, 19 drugs were detected with aqueous concentrations ranging from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Furthermore, there are potential cardiovascular disruptive compounds that are missed in the hit list due to lack of transcriptome profiling, as, for instance, cardiovascular pharmaceuticals that are designed for these purposes and occurring in the environment. 15,50 Despite these limitations, our approach via transcriptome profiling yields positive results and underpins the success in the confirmation of known and the discovery of unknown cardiovascular disruptors as verified by the following experimental data. Verification Experiments.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Furthermore, there are potential cardiovascular disruptive compounds that are missed in the hit list due to lack of transcriptome profiling, as, for instance, cardiovascular pharmaceuticals that are designed for these purposes and occurring in the environment. 15,50 Despite these limitations, our approach via transcriptome profiling yields positive results and underpins the success in the confirmation of known and the discovery of unknown cardiovascular disruptors as verified by the following experimental data. Verification Experiments.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
“…Thus, as a limitation of our concept, a few active compounds that lack investigation at different concentrations, or which do not fulfill all criteria, may not be identified due to different exposure times and concentrations and due to the lower number of affected genes. Furthermore, there are potential cardiovascular disruptive compounds that are missed in the hit list due to lack of transcriptome profiling, as, for instance, cardiovascular pharmaceuticals that are designed for these purposes and occurring in the environment. , Despite these limitations, our approach via transcriptome profiling yields positive results and underpins the success in the confirmation of known and the discovery of unknown cardiovascular disruptors as verified by the following experimental data.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Two studies examined concentrations of cardiovascular and lipid regulating drugs in effluent water released from municipal wastewater treatment plants, and in surface waters globally. Many cardiovascular drugs (58 of 82 drugs assessed in a systematic review of 322 studies, 13 and 19 of 26 drugs assessed in a recent primary study in Shanghai, China) 14 were detected in both types of waterways, in concentrations of up to several μg/L in wastewater and up to hundreds of ng/L in surface waters. ß-blockers, lipid regulating agents, ACE inhibitors, angiotension II receptor antagonists and diuretics were commonly studied and found in waterways, even after wastewater treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that pharmaceuticals present a threat to ecosystems and human beings in more than a quarter of the studied surface waters globally . Although wastewater treatment infrastructure has been continuously advancing, it is still insufficient to remove trace emerging contaminants, including many pharmaceuticals . As such, it is estimated that approximately 80% of pharmaceuticals are IOCs .…”
Section: Resultsmentioning
confidence: 99%